Efficacy and safety of long‐term low‐calorie diet in severely obese patients non‐eligible for surgery. Issue 3 (14th May 2013) - Alabdali, F.; Rueda‐Clausen, C. F.; Robbins, S.; Sharma, A. M.
Summary The aim of this study was to describe the long‐term efficacy and safety of low‐calorie diets (LCDs; providing 900 kcal day−1) in obese patients who have failed to achieve adequate weight loss with standard medical management and are non‐eligible for surgical therapeutic options. Charts from a regional hospital‐based outpatient bariatric programme were reviewed. Eight patients (75% male, age 60.1 ± 7.8 years) with severe obesity (body mass index 57.1 ± 8.8 kg m−2) and undergoing long‐term LCD (33 ± 10 months) were identified. Variables of interest included anthropometric, cardiovascular risk and nutritional parameters, thyroid, renal and liver function, changes in medications, side effects and adverse events. Average weight loss was 44 ± 15 kg (27 ± 13% of initial weight) at 24 months. Long‐term management with LCD resulted in substantial and sustained improvements in glucose homeostasis, blood pressure and lipid profile. LCD was well tolerated with minor self‐limited side effects. Over the follow‐up period, two subjects underwent coronary revascularization and one patient underwent knee replacement surgery – all recovered without complications. These findings suggest that in selected obese patients (non‐eligible for surgery), long‐term management with LCD may provide an alternative option for substantial and sustainable weight loss with significant improvements in metabolic and cardiovascular health.